METODOLOGI DALAM KAJIAN PSIKOLOGI ISLAM - Siti Faridah (Faculty of Ushuluddin and Humanities, 2016)
Initially Islamic Psychology studies and development made many Muslim scholars were spellbound by western psychology theories. They used them as a tool to analyze all sorts of phenomenon Muslim society and give the solution. It is important to remember that the Islamic Psychology concept should be built by the Muslim psychologists their selves. However, the western psychology concept is not necessarily suitable with the needs and purposes in Islam area. Because of that, the writer is interested to discuss the Islamic Psychology Methodology. Hopefully, Islamic Psychology can be an alternative way to solve Muslim society psychological problem especially and all of human being in generally. There were three approaches used by classic Muslim scholars to discuss psychic problem. They are skriptualis approach, falsafi/philosophy approach, and tasawwufi/Sufism approach. They are two studies in Islamic Psychology research; they are the theory and the method. Islam puts wahyu (divine revelation) as a religion paradigm which admits the existence of Allah in belief or in the implementation in the construction of science. Acsiologically, Islamic Psychology is built up to get the prosperity for human being. In epistemology, there is a relationship (nisbah) between mind and intuition. In ontology, it is for understanding human being as sunnatullah. Thus, al-Qur’an is the main source. Both of positivism and rationalism ideologies have different perspectives in finding the truth. Positivism believes that there is only one sensory truth. It could be observed and approved by anyone. In other side, Rationalism admits three truths. They are imperi-sensual truth, imperi-logic truth, and imperi-ethic. Both of the ideologies do not admit metaphysical and transcendental matters. As the result, the Islamic Psychology research will come true. Finally, to build up an Islamic Psychology as a branch of science, we still have so many things to do.